Willa Cather and the nineteenth century - Kaufman, Anne L.; Millington, Richard H., 1953- (Cather studies., 2015)
"Volume of essays exploring how nineteenth-century culture shaped Willa Cather's childhood, supplied her artistic models, generated her inordinate ambitions, and gave embodiment to the deeply held values present in her fiction"--